Sage-ing while age-ing - MacLaine, Shirley 1934- (Atria Books, a division of Simon & Schuster, Inc., 2008)
Over the years, Shirley has firmly established herself as a fearless, iconoclastic thinker and seeker of truth. Now, as she confronts the realities and rewards of growing older, she reflects on the greater understanding of her own place in the universe that her experiences have brought to her. Increasingly concerned with the potential pitfalls of modern medicine, she shares personal insights into nutrition, acupuncture, homeopathy, and alternative medicine. Moving beyond the physical, Shirley explores what has always interested her most--those things that are unseen. What is consciousness? What is the purpose of our lives? Are we alone in the universe? And perhaps the greatest mystery of all, what happens to us after death?--From publisher description.